Sustainable development and quality assurance in higher education : transformation of learning and society - Fadeeva, Zinaida; Galkute, Laima; Mader, Clemens; Scott, Geoff (Palgrave studies in global higher education, 2014)
"Higher education has a central role in helping our world address its interlaced social, cultural, economic and environmental challenges. Our universities and colleges can do this by identifying and testing solutions in collaboration with the regions they serve, and by building the leaders of tomorrow. But to do this higher education institutions (HEIs) must transform themselves, and this involves bringing together best practice in quality management and improvement for tertiary education with best practice in education for sustainable development. This book seeks to provide those interested in addressing this double helix of transformation with tested strategies and pathways for undertaking the journey successfully. It pays particular attention to dynamic interplays between organizational, national and international development in higher education policies and practices relevant for quality assurance. It also explores changing understandings of the notion of quality in higher education, relations of quality systems and other HEI strategies and questions of learner competences in the context of HEI strategies. "--